POLA PENGALOKASIAN PENDAPATAN PETANI CENGKEH DI DESA KIAWA I KECAMATAN KAWANGKOAN UTARA - Wandi Brafeli Lumintang; Juliana R. Mandei; Gene H.M. Kapantow (Sam Ratulangi University, 2016)
The objective of this research was to understandthe allocation pattern of clove farmers’ income at Kiawa 1 Village at the harvest time in 2014. This research was conducted in the Kiawa 1 Village for 3 months, from April 2015 to July 2015. Primary and secondary data were used in this research. The primary data were obtained by interviewing respondents using a list of questions (questionnaire). The secondary data were obtained from some relevant offices. Thirty respondents were randomly selected from 86 available farmers. Data were analysed descriptivelyusing some tables. The respondents were grouped based on their incomes, which were those with incomes less than 50 millions rupiahs and those with incomes of 50 millions rupiahs or above.The results showed that the income allocation pattern of the farmers' with income <50 million as follows:average consumption was Rp. 25,762,483.6 or 70.48%, average investment was Rp. 6396533.7 or 17.50%, and average savings was Rp. 4389871.4 or 12.01%. Moreover, the pattern for the group of farmers with income >50 million as follows: average consumption was Rp. 46,242,699.1 or 46.67%, average investment was Rp. 27,309,599.67 or 27.56% and average savings was Rp. 25,532,689.2 or 25.76%. The results indicated that the magnitude of the farmer's income affected the income allocation for consumption, investment and savings. As the farmers’ incomes increased the allocation for consumption tended to decrease while the allocation for investment and savings tended to increase.*ghmk*